Design of a low-profile super-gain end-fire slot antenna for UAV applications - He, Mingwei (Nanyang Technological University, 2022)
There are growing demands for unmanned aerial vehicles for various civil and military applications. It is noted that several antennas are mounted on the UAV for many on-board communication and radar systems. Such antennas should have a low profile and high gain. In this thesis, two cavity-backed double-slot antenna units working in the X band are designed. In the first design, two slots are etched out on the aluminium cavity to enhance the bandwidth and the realized gain. The simulation results show that this low-profile antenna has a 12.6% (1.26 GHz) bandwidth for S11 < -10 dB and a maximum realized gain of 8 dBi. In the second design, a wide slot is etched out on the aluminium cavity. This antenna has a 10.4% (1.04 GHz) bandwidth for S11 < -10 dB and a maximum realized gain of 6.17 dBi. In addition, two Hansen-Woodyard end-fire linear antenna arrays with 10 elements are built based on these antenna units. Both arrays show good radiation patterns and achieve gains of about 13.5 dBi.